2004
DOI: 10.1001/archopht.122.11.1680
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Iridectomy Histopathologic Features of Latanoprost- andNon–Latanoprost-Treated Patients

Abstract: To examine the histopathologic features of iridectomy specimens from patients undergoing glaucoma surgery and to compare histologic abnormalities in a group of patients with a history of latanoprost therapy with those in a group of patients who had no history of prostaglandin therapy (controls). Methods: Iridectomy specimens and patient history forms were submitted to the central Latanoprost Pathology Center. These were independently examined by 3 ophthalmic pathologists in a masked fashion. Specimens were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
(13 reference statements)
0
16
0
1
Order By: Relevance
“…Importantly, no malignant histological changes were observed. 21 Alm and coworkers recently reported clinical followup over five years. In 380 patients from the original regulatory trials, they observed that the number of adverse events did not differ between those patients with or without iris color change.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, no malignant histological changes were observed. 21 Alm and coworkers recently reported clinical followup over five years. In 380 patients from the original regulatory trials, they observed that the number of adverse events did not differ between those patients with or without iris color change.…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility of maltransformation of melanocytes as well as increased intraocular pressure due to pigmentation at the trabecular meshwork, which might decrease aqueous outflow. 8 Although no such complications have yet been reported, 6,[9][10][11] Arranz-Marquez et al 12 reported more changes in the iris than a simple increase in the melanin content of the melanocytes by histopathologic examination. Therefore, careful follow-up of patients with increased iris pigmentation by latanoprost treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that prostaglandin analogs do not increase the number of melanocytes (Albert, 2004). Histopathologic features of iridectomy specimens of patients on latanoprost were examined and found that latanoprost-induced iris color change was due to an increased amount of melanin within the melanocytes (Albert, 2004). No statistically significant increase was found in the number of melanocytes (Albert, 2004).…”
Section: Treatment Of Glaucomas Secondary To Intraocular Melanomasmentioning
confidence: 98%
“…Some concern regarding the use of prostaglandin analogs in patients with intraocular melanomas may exist. However, it has been shown that prostaglandin analogs do not increase the number of melanocytes (Albert, 2004). Histopathologic features of iridectomy specimens of patients on latanoprost were examined and found that latanoprost-induced iris color change was due to an increased amount of melanin within the melanocytes (Albert, 2004).…”
Section: Treatment Of Glaucomas Secondary To Intraocular Melanomasmentioning
confidence: 99%